ESCORPIÕES COLETADOS NUMA EXCURSÃO NOS ARREDORES DE MANAUS, AMAZONAS - Ferreira, Amilton; Fonseca, Osório M.; Cordeiro, Nelson (REVISTA DE AGRICULTURA, 2016)
ESCORPIÕES COLETADOS NUMA EXCURSÃO NOS ARREDORES DE MANAUS, AMAZONAS